Abundance of Meiofauna and Physical-Chemical Parameters as Water Quality Indicator - Muh Sri Yusal; Muh Aris Marfai; Suwarno Hadisusanto; Nurul Khakhim (Marine Science Department Diponegoro University, 2019)
The zone of Losari Coast is an icon of Makassar city, however increase activity of surrounding communities causes a decrease in the water quality. Meiofauna is an effective benthic organism used as an indicator of water quality. This study assessed the meiofauna abundance and physical-chemical parameters as water quality indicator in the Losari Coast, Makassar. The sampling method in this study was purposive sampling. The resuts showed that total meiofauna abundance identified was 66791 indv.m-2, composed of 12 phylum and 91 species or genera. Stations at the estuary of the Jeneberang and Tallo River are two sites with high level of abundance, this condition allows presence of organic contaminants triggers the high growth of meiofauna in these locations. Dissolved Oxygen is below its supposed level in waters. Acidity, phosphate and nitrate content at some of research stations exceed the threshold of their allowed presence in waters set by Indonesia government. Ostracoda, oligochaeta, polychaeta, tunicata and ciliophora are phylums with a high level of abundance, because the phylum has high adaptability to pollutant. Good water quality is indicated by a variety of biota living in the waters, the range of diversity and uniformity indices shows that meiofauna species are categorized highly diverse and evenly distributed. The dominance index shows that there is no species was dominant, except stations around Losari reclamation project. Temperature, current velocity, depth, brightness, salinity, pH, DO, nitrate-seawater, and phosphate-seawater correlate with meiofauna abundance. The results as a consideration for the management or monitoring of coastal environments.